2021
DOI: 10.1177/17534666211028072
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CASC2 is involved in the development of chronic obstructive pulmonary disease via targeting miR-18a-5p/IGF1 axis

Abstract: Aims: Chronic obstructive pulmonary disease (COPD) is a systemic disease. Several long non-coding RNAs (lncRNAs) have been identified to be aberrantly expressed in COPD patients. This study investigated the role of lncRNA cancer susceptibility candidate 2 (CASC2) in COPD, as well as its potential mechanism. Methods: Fifty smokers with COPD and another 50 smokers without COPD were recruited. Receiver operating characteristic curve was constructed to assess the diagnostic value of CASC2 in COPD patients. 16HBE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Furthermore, ceRNA networks have also been reported to regulate the progression of COPD. lncRNA SNHG5, cancer susceptibility 2 and RP11-86H7.1 have all been reported to serve as miRNA sponges and keep miRNA away from its target genes through ceRNA networks to serve important roles in the progression of COPD ( 28 , 68 , 69 ). However, to the best of our knowledge, at present, no study has reported the role of GAS5 in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ceRNA networks have also been reported to regulate the progression of COPD. lncRNA SNHG5, cancer susceptibility 2 and RP11-86H7.1 have all been reported to serve as miRNA sponges and keep miRNA away from its target genes through ceRNA networks to serve important roles in the progression of COPD ( 28 , 68 , 69 ). However, to the best of our knowledge, at present, no study has reported the role of GAS5 in COPD.…”
Section: Discussionmentioning
confidence: 99%
“… 10 The above evidence reveals that lncRNA CASC2 hinders organ injuries through various pathways. 10 , 11 , 12 , 17 , 19 Thus, this study further assessed the relationship between lncRNA CASC2 and multi‐organ injuries in sepsis patients. It was clear that lncRNA CASC2 was inversely linked with multiple organ injuries (reflected by total SOFA score), as well as respiratory, coagulation, liver, and renal injury (reflected by SOFA sub‐scales) in sepsis patients.…”
Section: Discussionmentioning
confidence: 99%
“…CSE was prepared according to the previously reported method [ 16 ]. In short, a cigarette burns with a modified apparatus with a driving device.…”
Section: Methodsmentioning
confidence: 99%